Luminescent Eu3+ doped silicate-aluminum-borate hybrid materials obtained by photopolymerization of sol-gel resins - Tayama, Gabriel Toshiaki; Costa, Beatriz Helena [UNESP]; Caixeta, Fábio José [UNESP]; Murback Filho, Renato Pereira; de Oliveira Junior, Marcos; Elias e Silva, Lucas Toth [UNESP]; Messaddeq, Younes [UNESP]; Santagneli, Silvia Helena [UNESP] (Springer Nature, 2025)
Hybrid sol-gel materials incorporating components like phosphates and borates can serve as hosting matrices of significant relevance for lanthanides, since they can efficiently coordinate the rare earth ion to enhance its luminescence. The soft chemistry inherent to this method allows the production of monolithically transparent fluorescent materials without the need of energy-intensive processes typical of conventional lanthanide-doped glasses and monocrystals. We present the synthesis and luminescence of transparent Eu3+ doped silicate-aluminum-borate hybrid materials. The materials were developed via the photopolymerization of resins produced by the sol-gel process, and their structure was analyzed using infrared, Raman and solid-state nuclear magnetic resonance (NMR) spectroscopies. Our findings demonstrated an amorphous, and highly condensed inorganic structure composed by boroxol and aluminum-silicate units which show small interaction with each other. NMR results elucidated that borate species tend to homocondensate in the presence of the aluminum alkoxide, which promptly heterocondensates with the alkoxysilane to form an aluminum-silicate network. Samples with a stoichiometry of 90Si, 5Al, and 5B were doped with varying concentrations of Eu3+, and their luminescent properties were investigated. The luminescence of Eu3+ was detected despite the elevated concentration of hydroxyl groups in the materials and absence of thermal treatment, with luminescence lifetime comparable to other silica matrices obtained by thermal treatment. These materials are interesting candidates for additive manufactured active photonic devices, luminescent optical fibers manufacturing, and printable integrated photonics.Graphical AbstractGraphical Abstract: Transparent silicate-aluminum-borate hybrid materials structure elucidated by solid state NMR and luminescence spectra when doped with europium.